Impact of Total Quality Management Practices on Sustainability And Company Performance: A Case Study of Miro Forestry Company Ltd in Mile 91, Sierra Leone (International Journal of Scientific Research and Management (IJSRM), 2024)
Organizations globally are increasingly adapting to dynamic business environments, where management must consistently identify strategies to maintain or enhance competitive advantage. Total Quality Management (TQM) has emerged as a critical approach for manufacturing firms seeking to improve operational efficiency and effectiveness. Although previous research has explored the relationship between TQM practices and organizational performance, the findings have been inconclusive, signaling the need for further investigation. Notably, in Sierra Leone, limited research exists on the effect of TQM on the performance of manufacturing firms, revealing a knowledge gap. This study addresses this gap by examining the impact of TQM practices on the performance of manufacturing firms in Sierra Leone, with a specific focus on Miro Forestry Company Ltd. The main objectives of the study are to: (1) assess the impact of customer focus on organizational performance, (2) evaluate the role of top management commitment in enhancing performance, (3) examine the effect of continuous improvement on performance outcomes, and (4) determine the influence of employee involvement on organizational performance. The study employed a descriptive quantitative research design. A sample of 121 employees was selected from a target population of 400 using stratified random sampling. Data were collected through self-administered questionnaires and analyzed using SPSS alongside correlation analyses to assess relationships between variables. The findings were presented using figures and tables. Results show that TQM practices, which mainly involve customer focus, top management commitment, continuous improvement, and employee involvement were found to positively impact organizational performance. Customer focus significantly enhances customer satisfaction, while top management commitment and continuous improvement contribute to overall performance. Employee involvement also positively influences performance outcomes. The study recommends that companies should foster a robust organizational culture characterized by trust, respect, and a shared sense of purpose. Additionally, continuous improvement should remain a central focus to sustain performance. Management is also advised to prioritize quality management by motivating employees and offering incentives to support TQM initiatives.